Gene disruption by cell-penetrating peptide-mediated delivery of Cas9 protein and guide RNA - Ramakrishna, Suresh; Kwaku Dad, Abu-Bonsrah; Beloor, Jagadish; Gopalappa, Ramu; Lee, Sang-Kyung; Kim, Hyongbum (Genome Research, 2014)
RNA-guided endonucleases (RGENs) derived from the CRISPR/Cas system represent an efficient tool for genome editing. RGENs consist of two components: Cas9 protein and guide RNA. Plasmid-mediated delivery of these components into cells can result in uncontrolled integration of the plasmid sequence into the host genome, and unwanted immune responses and potential safety problems that can be caused by the bacterial sequences. Furthermore, this delivery method requires transfection tools. Here we show that simple treatment with cell-penetrating peptide (CPP)–conjugated recombinant Cas9 protein and CPP-complexed guide RNAs leads to endogenous gene disruptions in human cell lines. The Cas9 protein was conjugated to CPP via a thioether bond, whereas the guide RNA was complexed with CPP, forming condensed, positively charged nanoparticles. Simultaneous and sequential treatment of human cells, including embryonic stem cells, dermal fibroblasts, HEK293T cells, HeLa cells, and embryonic carcinoma cells, with the modified Cas9 and guide RNA, leads to efficient gene disruptions with reduced off-target mutations relative to plasmid transfections, resulting in the generation of clones containing RGEN-induced mutations. Our CPP-mediated RGEN delivery process provides a plasmid-free and additional transfection reagent–free method to use this tool with reduced off-target effects. We envision that our method will facilitate RGEN-directed genome editing.